2006
DOI: 10.1111/j.1399-6576.2006.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of μ‐opioid receptor gene polymorphism (A118G) with variations in morphine consumption for analgesia after total knee arthroplasty

Abstract: Background: Morphine consumption after a given surgical procedure can vary considerably. Studies show that single nucleotide polymorphism involving the nucleotide position 118 at exon 1 of the m-opioid receptor gene (OPRM1) may play a role in mediating the effects of opioids. This study was performed to correlate the A118G polymorphism at OPRM1 with morphine consumption in patients undergoing total knee arthroplasty. Methods: Post-operative pain was relieved by patient-controlled analgesia (PCA). The analgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
175
5
11

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(201 citation statements)
references
References 18 publications
10
175
5
11
Order By: Relevance
“…morphine via patient-controlled analgesia [10,11,14,23]. In these various settings, patients with at least one 304G allele exhibited a trend towards increased systemic morphine requirements, findings which are in the opposite direction to our results with intrathecal fentanyl.…”
Section: Discussioncontrasting
confidence: 55%
“…morphine via patient-controlled analgesia [10,11,14,23]. In these various settings, patients with at least one 304G allele exhibited a trend towards increased systemic morphine requirements, findings which are in the opposite direction to our results with intrathecal fentanyl.…”
Section: Discussioncontrasting
confidence: 55%
“…Few studies have investigated the effect of the Il8A>G polymorphism on post-operative pain or its interaction with other opioids. Two studies were conducted on an Asian population undergoing scheduled gynaecological and orthopaedic surgery: they received POP therapy with morphine by means of PCA (Patient-Controlled-Analgesia) over 48 h: female G 118G homozygotes needed more morphine (33± IOmg) in the first postoperative day than A l18G heterozygotes (29±8mg) or wild-type (27± 1Omg) (19,20). More recently, a study conducted on 138 Japanese patients, undergoing major open abdominal surgery, confirmed that G118G homozygous Assessed for eligibility (n=801 consecutive scheduled surgery'patients)…”
Section: Discussionmentioning
confidence: 99%
“…Так, Chou и соавт. показали, что при контролируемой пациентом аналгезии в раннем послеоперационном пе риоде после выполнения артропластики коленного сус тава носители генотипа 118G/G суммарно вводили себе большие дозы морфина (40,4±22 мг) по сравнению с но сительницами генотипа 118A/G (25,6±11,7 мг) и 118A/А (25,3±15,5 мг) [46]. В этом же исследовании по казано, что пациенты чаще вводили себе наркотический аналгетик по сравнению с носителями других геноти пов.…”
Section: Introductionunclassified